Hybrid virtual screening identifies dipyrazole carboxamide derivatives as novel direct InhA inhibitors with antitubercular activity - Punkvang, Auradee; Pakamwong, Bongkochawan; Phusi, Naruedon; Thongdee, Paptawan; Chayajarus, Kampanart; Sangswan, Jidapa; Pangjit, Kanjana; Suttisintong, Khomson; Leanpolchareanchai, Jiraporn; Hongmanee, Poonpilas; Santanirand, Pitak; Spencer, James; et al. (Biochimica et biophysica acta. General subjects, 2025)
Direct inhibitors of M. tuberculosis enoyl-acyl carrier protein reductase (M. tuberculosis InhA) remain effective against variants with mutations associated with isoniazid resistance. In our previous study, structure-based virtual screening was employed to discover such inhibitors. However, most identified hits exhibited limited antimycobacterial activity, with minimum inhibitory concentration (MIC) values of >100 μg/mL. To address this challenge, we refined our virtual screening strategy by integrating ligand- and structure-based virtual screening approaches. The efficacy of this hybrid virtual screening approach was validated through biological assays measuring MIC and half-maximal inhibitory concentration (IC50) for the inhibition of M. tuberculosis growth and InhA activity, respectively. Among 14 identified hits, compounds 3 and 10, classified as dipyrazole carboxamide derivatives, were validated as promising lead candidates, with MIC values of 25 and 50 μg/mL and IC50 values of 10.60 ± 0.56 and 5.08 ± 0.30 μM, respectively. The relatively low hit-to‑lead conversion rate (14 %) is ascribed to our observation that nine of the identified hits, including compounds 3 and 10, showed some level of precipitation in the MIC assay medium. Molecular dynamics simulations show that the dipyrazole carboxamide moiety in compounds 3 and 10 forms essential hydrogen bonds with nicotinamide adenine dinucleotide (oxidized form) (NAD+) in the InhA binding pocket. Notably, both compounds 3 and 10 exhibit favorable safety profiles, with no toxicity observed in Caco-2 cells at concentrations up to 100 μg/mL. Consequently, we believe that these compounds present promising starting points for further lead optimization and development of novel antitubercular agents. [Display omitted] •Hybrid virtual screening identified potent direct M. tuberculosis InhA inhibitors.•Compounds 3 and 10 showed low MICs and strong InhA binding interactions.•Lead compounds exhibited no cytotoxicity in Caco-2 cells up to 100 μg/mL.